Canadian Stroke Best Practice Recommendations: Telestroke Best Practice Guidelines Update 2017. Issue 8 (October 2017) - Blacquiere, Dylan; Lindsay, M Patrice; Foley, Norine; Taralson, Colleen; Alcock, Susan; Balg, Catherine; Bhogal, Sanjit; Cole, Julie; Eustace, Marsha; Gallagher, Patricia; Ghanem, Antoinette; Hoechsmann, Alexander; et al.
Every year, approximately 62, 000 people with stroke and transient ischemic attack are treated in Canadian hospitals. The 2016 update of the Canadian Stroke Best Practice Recommendations Telestroke guideline is a comprehensive summary of current evidence-based and consensus-based recommendations appropriate for use by all healthcare providers and system planners who organize and provide care to patients following stroke across a broad range of settings. These recommendations focus on the use of telemedicine technologies to rapidly identify and treat appropriate patients with acute thrombolytic therapies in hospitals without stroke specialized expertise; select patients who require to immediate transfer to stroke centers for Endovascular Therapy; and for the patients who remain in community hospitals to facilitate their care on a stroke unit and provide remote access to stroke prevention and rehabilitation services. While these latter areas of Telestroke application are newer, they are rapidly developing, with new opportunities that are yet unrealized. Virtual rehabilitation therapies offer patients the opportunity to participate in rehabilitation therapies, supervised by physical and occupational therapists. While not without its limitations (e.g., access to telecommunications in remote areas, fragmentation of care), the evidence-to-date sets the foundation for improving access to care and management for patients during both the acute phase and now through post stroke recovery.